PENGARUH KUALITAS PELAYANAN PUBLIK TERHADAP KEPUASAN MASYARAKAT DI KECAMATAN SALAHUTU KABUPATEN MALUKU TENGAH - Natalia Amba; Saul Ronald Jacob Saleky; Olivia Laura Sahertian (Jurnal Administrasi Terapan, 2023)
The quality of public services is all forms of activity carried out by the government in order to meet the expectations of the community. Community satisfaction is the community's response to the evaluation of the perceived discrepancy between expectations and the results obtained. Many factors result in community satisfaction not being met, one of which is the service provided is not of good quality such as employees not treating the community well, available infrastructure is inadequate, there is no certainty of time and cost in the service process, still discriminating between communities in providing services, and employees are unethical polite and friendly in providing services. This study aims to examine and analyze the effect of public service quality on community satisfaction at the Salahutu District, Central Maluku Regency. 64 respondents were taken as a sample with the requirements of having used the services of the Suli Village Office more than twice and being at least 17 years old. Sampling using purposive sampling technique. The data analysis method used is quantitative analysis, namely validity and reliability tests, classical assumption tests, simple regression analysis, t tests and coefficient determinant tests. Based on the results of the t test and determination coefficient value. it shows that the quality of public services has a positive and significant effect on community satisfaction. From the findings of this study, it shows that the Suli Village Office must continue to improve the quality of public services, this is done in order to maximize community satisfaction because the quality of public services affects community satisfaction.Keywords: quality of public services, community satisfaction